2022
DOI: 10.7759/cureus.25466
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Cervical Canal Using Computed Tomography Scan Among Patients With Neck Pain in North India

Abstract: Introduction Cervical spinal stenosis is a common disease that results in considerable morbidity and disability. To avoid long-term disability caused by irreversible spinal cord damage, quick diagnosis and treatment are required. To our knowledge, until recently, there has been no report or study evaluating the cervical canal stenosis and associated facet joint arthrosis as the major cause of neck pain, so the current study used computed tomography (CT) scans to determine the prevalence of cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It distributes the load on the joint surfaces equally and acts as a cushion. IVDs, which are generally 2/5 of the vertebral height, consist of nucleus pulposus in the inner part and annulus fibrosus in the outer part [1][2][3][4]13,[22][23][24][25][26][27] . Early recognition and diagnosis of any pathology or deviation from normality involving the cervical intervertebral disc can help prevent and delay morphological deterioration that may pose a serious risk in the future 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It distributes the load on the joint surfaces equally and acts as a cushion. IVDs, which are generally 2/5 of the vertebral height, consist of nucleus pulposus in the inner part and annulus fibrosus in the outer part [1][2][3][4]13,[22][23][24][25][26][27] . Early recognition and diagnosis of any pathology or deviation from normality involving the cervical intervertebral disc can help prevent and delay morphological deterioration that may pose a serious risk in the future 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The cervical vertebrae's body is the lowest. Also, tumors, infections, trauma, and degenerative changes such as intervertebral disc herniation, and osteophytes can induce the cervical canal to narrow 13 . Morishita et al suggested that a cervical spinal canal diameter of less than 13mm might predispose to the development of pathological changes in the cervical intervertebral discs, and the presence of a congenitally narrow canal may be an important reason for the development of cervical spinal stenosis 14 .…”
Section: Introductionmentioning
confidence: 99%